Study on the dissolution diffusion behavior of Al in Sn melt - Zhao, Junfeng; Li, Xiaohui; Xie, En; Mei, Haijuan; Shen, Youqu; Li, Kai; Gong, Weiping; Wang, Liang (Frontiers in Materials, 2023)
The Al-Sn alloys with a large melting point difference and large density are widely used in sliding bearings in the aerospace and automobile industries. But the problem of insufficient alloying easily occurs during the preparation process due to the physical properties. This paper investigates the dissolution and diffusion behavior of Al in Sn Melt. The dissolution rates of Al in Sn melts at different temperatures were calculated. The research results show that the Al/Sn diffusion is dominated by the diffusion of Sn into Al, the Sn melt penetrate into the solid Al to form diffusion channel leading to the exfoliation and aggregation of the unmelted Al particles. Then, an electromagnetic field treatment technology was introduced to improve sufficient alloying by regulating the flow field of the metal melt. It can accelerate the diffusion and redistribution of elements at the Al/Sn solid-liquid interface, as well as change the dissolution mechanism of Al/Sn interface.